HETEROSIS AND COMBINING ABILITY STUDIES IN OKRA [ABELMOSCHUS ESCULENTUS (L.) MOENCH] FOR YIELD AND QUALITY PARAMETERS - G. C. NAGESH; R. MULGE; V. RATHOD; L. B. BASAVARAJ; S. M. MAHAVEER (The Bioscan, 2014)
A study was conducted in okra to estimate the magnitude of heterosis and to identify the good combiners for yield and quality parameters. Fifty four F1 hybrids generated by line x tester mating design these F1 s along with 21 parents and commercial check were evaluated in a randomized block design with two replications at K.R.C. College of Horticulture, Arabhavi, Gokak Taluk, Belagavi district of Karnataka. Appreciable heterosis was found over better parent and commercial check for all the traits studied in desirable direction. The maximum positive heterosis was observed in the cross KON-8 x IC90174 over better parent (107.90%) and the commercial check (92.42%) for total yield per hectare.The crosses KON-8 x IC90174 (92.42%), KON-5 x AAN (45.83%), KON-16 x AAN (40.52%), KON-12 x AAN (35.07%) and KON-7 x IC90174 (27.11%) showed significant heterosis over the commercial check in order of meritfor total yield per hectare. The line KON-5 for fruit length (1.31), fruit diameter (1.87), average fruit weight (2.53), total yield per plant (35.40) and for total yield per hectare (2.18), KON-6 (1.87) for number of fruits per plant, KON-4 (0.33) for number of locules per fruit and KON-15 (9.03) for number of seeds per fruit were identified as good general combiners. In order of merit the crosses KON-8 x IC90174 (6.55), KON-16 x AAN (2.95), KON-5 x AAN and KON-17 x KON-19 (2.04) and KON-18 x IC90174 (2.00) were identified as good specific combiners. The present study reveals good scope for commercial exploitation of heterosis in okra.